Pengaruh Kepemimpinan dan Kompetensi terhadap Kinerja Pegawai Pada Kantor Kecamatan Tanralili Kabupaten Maros - Muhammad Alwi Haruna (Jurnal Manajemen Bisnis Era Digital, 2025)
The Effect of Leadership and Competence on Employee Performance at the Tanralili District Office, Maros Regency. Thesis Management Study Program of the Indonesian Institute of Education Management (STIM-LPI) Makassar, supervised by Dr. Andi Irfan, SE., M.Si and Dr. Amiruddin, S.Ag., M.Ag This research is to determine the effect of leadership and competence partially and the joint influence between leadership and competence on employee performance at the Tanralili sub-district office, Maros Regency. The object of this research is the tanralili sub-district office in maros district. The type of research used is quantitative research by distributing questionnaires via google from. The sample amounted to 32 civil servants. The results of this study indicate that the partial test of Leadership has a significant effect of 0.001 or below 0.05 while Competence also has a positive effect, while simultaneously has a significant effect of 0.001 <0.0 with an F value of 48,243.